Palestinian Chicago Identity in Exile - Lybarger, Loren D. (University of California Press, 2020)
Chicago is home to one of the largest, most politically active Palestinian immigrant communities in the United States. For decades, secular nationalism held sway as the dominant political ideology, but since the 1990s, its structures have weakened and Islamic institutions have gained strength. Drawing on extensive fieldwork and interview data, Palestinian Chicago charts the origins of these changes and the multiple effects they have had on identity across religious, political, class, gender, and generational lines. The perspectives that emerge through this rich ethnography challenge prevailing understandings of secularity and religion, offering critical insight into current debates about immigration and national belonging.